Kendala Implementasi Penilaian Autentik Selama Masa Pandemi Covid-19 di Tingkat Sekolah Dasar - Fajar Octavia Widiasari; Tjipto Subadi; Achmad Fathoni (Cakrawala: Jurnal Pendidikan, 2021)
The aim of the study is to explore: (1) the implementation of authentic assessment in elementary schools, (2) the obstacles of teachers in carrying out authentic assessments in elementary schools, (3) solutions to minimize obstacles in the implementation of authentic assessments in elementary schools. The research method uses qualitative research. The samples used were fourth, fifth, and sixth-grade teachers who were randomly selected. Collecting data through interviews, observation, and documentation. Triangulation technique used to estimate the validity of data. Data analysis uses reduction, presentation, and conclusion techniques. The results showed that (1) the implementation of authentic assessments in schools had not gone well, (2) the teacher had problems in entering students' final grades into their report cards, the lack of students' ability to understand questions and obstacles in implementing the skills domain, which took a lot of funds so that sometimes not going well, (3) the solution offered to minimize the constraints of authentic assessment is a change in the authentic assessment paradigm which is more flexible. The flexibility of authentic assessment can be achieved by utilizing digital-based assessments because the assessment system can be done at any moment.